ENHANCING THE INFLUENCE OF ORGANIZATIONAL COMMUNICATION ON THE PERFORMANCE OF LOCAL GOVERNMENT OFFICIALS IN TIDORE ISLANDS - Abd. Kadir, Iriyani; Rumaisha Alwi, Zulaikha (PT. Sangadji Media Publishing, 2023)
The reform of the public sector is a crucial aspect of development and the enhancement of government efficiency. One vital element within this reform is the improvement of the performance of public officials, encompassing various stages in budget management, including planning, approval, implementation, and public fund accountability. This study has a clear objective, which is to identify the impact of organizational communication on the performance of government officials. In the context of Tidore Islands, the research population involves the Regional Work Units (SKPD), which play a significant role in local governance. Data for this research was collected through the distribution of questionnaires to 250 respondents from each SKPD. The use of these questionnaires aims to test the research hypothesis, which suggests that organizational communication has a significant influence on the performance of government officials. Data analysis results reveal a strong correlation between effective organizational communication and government officials' performance. This finding provides empirical evidence supporting the importance of good communication in enhancing the performance of local government, ultimately contributing to the realization of a more efficient and transparent public sector reform. Thus, this research makes a significant contribution to the development of better public policy and management practices in Tidore Islands.